Difficulties in the Implementation of Sustainable Consumption in the Post-modern Era of Acceleration - Leźnicki, Marcin (Studia Ecologiae et Bioethicae, 2021)
This article presents the difficulties that prevent the implementation of sustainable consumption, in conditions of the neo-liberal free market economy. In order to better illustrate this topic, the article has been divided into two parts. The first one describes the reasons for not implementing the idea of sustainable consumption, which is the basis of sustainable development. In order to better clarify these reasons, this part also describes in detail, the concept of sustainable consumption, how it is perceived by society, and its related axiology. Moreover, qualitative characteristics of sustainable consumption are presented. The second part presents the idea of accelerated consumption, postulated by post-modernism, and being the basis of the post-modern era of acceleration. It also details the optimal adjustment of accelerated consumption to the era of fast-flowing time, and requirements of the free market economy, oriented on income optimalisation. Furthermore, it points at quantitative characteristics of accelerated mass consumption, and new consumer axiology brought about by post-modernism. Finally, the main differences between these two types of consumption, and the conditions for implementing accelerated consumption in the post-modern era of acceleration, are presented.